Influence of Ambient Air on Cell Reactions of Li-air Batteries. (10th February 2016) - Huang, Shiting; Cui, Zhonghui; Zhao, Ning; Sun, Jiyang; Guo, Xiangxin
Highlights: Li-air batteries with TEGDME-based electrolytes could cycle in ambient air. The discharge products were Li2 O2 initially and eventually Li2 CO3 . The Li anodes turned LiOH after cycles in ambient air. Thin polymer-layer protected Li anodes could extend the cycle number. Abstract: The non-aqueous Li-air battery offers the highest theoretical energy density among currently available rechargeable storage units. However, H2 O and CO2 in air are viewed as detrimental factors which hinder its performance. Thus, most previous researches focus on the Li-oxygen battery with pure O2 as working atmosphere. The actual influence of ambient air on the cell chemistry has seldom been investigated. Here, we carry out study of the Li-air batteries with tetraethylene glycol dimethyl ether (TEGDME)-based electrolytes and carbon-nanotube-based cathodes operated in ambient air. The cells show the specific capacity as large as 7000 mAh g −1 upon the first discharge to 2 V and more than 50 cycles when being operated with the capacity cutoff of 500 mAh g −1 . It is found that the TEGDME-based electrolytes slightly decompose during cell operation. Li2 O2 forms during initial discharge and turns Li2 CO3 and LiOH owing to its reaction with CO2 and H2 O. The lithium anodes become expanded and pulverized after cycles, the problem of which can be relieved by protection with coated polymer layers. These results give essential information that would be helpful for development of the practical Li-air batteries operated in ambient atmosphere.